If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + z)(5z + 3) = 0 Reorder the terms: (9 + z)(3 + 5z) = 0 Multiply (9 + z) * (3 + 5z) (9(3 + 5z) + z(3 + 5z)) = 0 ((3 * 9 + 5z * 9) + z(3 + 5z)) = 0 ((27 + 45z) + z(3 + 5z)) = 0 (27 + 45z + (3 * z + 5z * z)) = 0 (27 + 45z + (3z + 5z2)) = 0 Combine like terms: 45z + 3z = 48z (27 + 48z + 5z2) = 0 Solving 27 + 48z + 5z2 = 0 Solving for variable 'z'. Factor a trinomial. (9 + z)(3 + 5z) = 0Subproblem 1
Set the factor '(9 + z)' equal to zero and attempt to solve: Simplifying 9 + z = 0 Solving 9 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + z = 0 + -9 z = 0 + -9 Combine like terms: 0 + -9 = -9 z = -9 Simplifying z = -9Subproblem 2
Set the factor '(3 + 5z)' equal to zero and attempt to solve: Simplifying 3 + 5z = 0 Solving 3 + 5z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5z = 0 + -3 5z = 0 + -3 Combine like terms: 0 + -3 = -3 5z = -3 Divide each side by '5'. z = -0.6 Simplifying z = -0.6Solution
z = {-9, -0.6}
| 5x^3+40x^2+60x=0 | | Z=23 | | 2x-8+2=x-3+5 | | f(x)=x^3+2x^2-8x-5 | | 4x(2x-1)^1/2 | | n^2-19n+10=0 | | 7(3-z)6=-z | | 1/3x+2=1/6x+4/3 | | 3y=2x+b | | 3(x+7)-2x=3+2x | | Y=x^4-3x^2 | | 28=4b-3s | | -3+5x+30=37 | | 28=4b+3s | | -8(3+r)=32 | | 3/3-4 | | -3(2h+1)=4h-3 | | .15-c=1.105 | | -3(-5)(-7)(-1)= | | -8(3+r)=42 | | 8-3*5+2= | | 2x+5x+3=-3x+23 | | 3y-2=2y+2 | | 3/8-4/9 | | -5(-3)(-1)(2)= | | 3/9-4/9 | | 45=2(3x-1)+4x | | v/8=8 | | 010(x+80)+0.20x=8+0.30x | | 14-4p=34 | | 6m+11=8m+3 | | (m-n+k)(m+2n-3k)=0 |